An overview of municipal solid wastes generation in Malaysia - Tarmudi, Zamali; Abdullah, Mohd Lazim; Md. Tap, Abu Osman (Universiti Teknologi Malaysia, 2009)
Increasing population and tremendous urbanisation growth and other factors influence directly the municipal solid waste (MSW) generation in Malaysia. The huge quantity of MSW generation, particularly in Peninsular Malaysia, has increased from 16,200 tonnes per day in 2001 to 19,100 tonnes per day in 2005 or an average of 0.8 kg/capita/day. The amount increases yearly and seems to grow in parallel with the urban areas in many Asian countries which are estimated to produce approximately 8 million tonnes per day. Thus, this paper briefly discusses the scenario of MSW generation in Malaysia. It focuses on the trends of MSW generation, the composition of MSW, the contributing factors as well as the management problems occurring in Malaysia presently. In addition, some updated statistical figures related to the MSW and management aspects are provided to clarify the present situation and the government’s future planning. Recent development indicates that the Malaysian government has taken forward to deal with such problems in MSW management across the municipalities through closed dumping sites, upgrading existing conventional landfills to sanitary status, constructing new transfer stations and giving serious priority for an alternative disposal system in the near future. Moreover, the establishing a new national solid waste and public cleansing management corporation and enacted a new specific regulations for solid waste and public cleansing management which approved on September 2007 is also seen as a proactive step towards achieving the sustainability of MSW management as a long term solution.